Scribal Education in the Sargonic Period - Kraus, Nicholas L. (Harvard Semitic Studies, 2021)
Scribal Education in the Sargonic Period is an in-depth analysis of the process of education for scribes during the period of Sargonic hegemony in ancient Mesopotamia (c. 2335-2150 BCE). The book provides a holistic study of the topic, addressing the technology of writing, the school texts used in education, the languages of instruction, and the social and historical context of scribal life and an education in cuneiform writing. The topic of scribal education at such an early period of Mesopotamian history has never been addressed at length before. Nicholas Kraus convincingly argues that scribal education during the Sargonic period was closely tied to the administrative institutions of the Sargonic Empire and prepared a scribe to become an effective administrator. The Harvard Semitic Studies series publishes volumes from the Harvard Museum of the Ancient Near East. Other series offered by Brill that publish volumes from the Museum include Studies in the Archaeology and History of the Levant and Harvard Semitic Monographs , https://hmane.harvard.edu/publications.